Israel Kirzner On Dynamic Efficiency And Economic Development - Espinosa, Victor; Wang, William; Zhu, Haijiu Zhu (REVISTA PROCESOS DE MERCADO, 2020)
Israel Kirzner lays the foundations of entrepreneurship as the driving force of the market process by referring to alertness, uncertainty, and plan coordination. His approach, following the footsteps of Mises and Hayek, legitimizes entrepreneurial creativity and profit-making as the heart of the dynamic market process. He argues that an accurate insight into the economic system requires exploring how entrepreneurial dynamics work in society. This statement contrasts with the theories and models that govern modern development economics, such as randomized controlled trials (RCTs), in which the zero-intelligence agents replace the flesh-and-blood entrepreneur. Randomized controlled trials are considered the gold standard in modern development economics to assess treatment intervention efficacy in underdeveloped countries (Rodrik 2009). As a causal inference method, RCTs seek to determine whether a program had the outcome for which it was designed. Experts often utilize purely quantitative and experimental strategies for their guiding insights through trial and error of different interventions. In the ethics domain, experts seek to maximize the cost-benefit of specific interventions subject to a given set of data to rectify the inequalities generated by the market economy in underdeveloped economies. The economist becomes a kind of plumber who designs the creation and distribution of the “social pie,” assigning the respective slices to the specific individuals who participate in the experiments. Consequently, RCTs have justified active government intervention in the market process on behalf of policy advisers.However, Kirzner’s theory of entrepreneurship indicates that modern development economics’s core problem is epistemological and related to using the criterion of static efficiency in applied economics. Although RCTs are considered one of the most rigorous methods to inquire into the effectiveness of development policies, their design lacks interpretative capacity on the essence of economic phenomena. Experts on RCTs do not recognize that economic development is the byproduct of achieving social cooperation and coordination driven by purposeful human action under the division of labor. If the essence of economic phenomena is disregarded, it is impossible to address poverty causes adequately. Accordingly, RCTs are limited to testing cosmetic problems of economic underdevelopment.This article does not seek to offer specific proposals to remedy RCTs’ shortcomings, but it provides a theoretical foundation to guide further theoretical and empirical work. It argues that development economists have overlooked Kirzner’s theory of efficiency, which cannot be omitted without impairing the premise that development theory involves studying the dynamic process of plan coordination. Its relevance lies in the fact that Kirzner’s research can reshape modern development economics, which implies a theoretical advancement in several areas:• Kirzner’s analysis of static efficiency reveals the epistemological and ethical problems of modern development economics.• The framework of Kirzner’s dynamic efficiency clarifies the role of entrepreneurship in understanding how the market works.• Dynamic efficiency recognizes the creative and coordinating potential of entrepreneurship and capital accumulation in economic development.• Kirzner’s economic development theory responds to ethical dilemmas about (in)equality and pure profit within a market economy.• Contemporary research on dynamic efficiency explores new branches, such as the role of psychology, culture, and morality in economic development.Most research on efficiency and underdevelopment is still packaged in mathematical models that reduce the market’s complexity to comparative statics. Fortunately, a growing number of theories have begun to challenge this state of affairs by examining the following: First, psychology’s impact on productivity or the unproductiveness of entrepreneurial profit opportunities. Second, the role of culture in the dynamic process of institutional change and the adaptation of the entrepreneurial performance that ensures or deter economic development. Third, the relationship between personal morality and dynamic efficiency concerns private property and contractual ties. Hence, there are several strands of new literature on dynamic efficiency and development economics. This article focuses on one aspect that concerns both economists and governments in terms of modern thinking and practice: the role of efficiency (static and dynamic) in economic development.